'Falling Awake': Peter Manson's Catachresis. Issue 1 (21st January 2020) - Gardner, Callie
Abstract : One of the key tropes of Peter Manson's work is the deliberately misleading, decontextualised, and downright erroneous use of words, which this article seeks to categorise under the rhetorical trope of catachresis or abusio, misuse. The traditional rhetorical distinction holds that catachresis is only used when there is no adequate term for what one wishes to describe, and that if the term does exist, it is metaphor. However, the Roman rhetorician Quintilian admits (reluctantly and without offering up examples) that 'poets are accustomed' to breaking this rule and using catachresis for other reasons, as it seems they have always done. A productively catachresis-centred poetics like that practiced by many avant-garde poets leading up to Manson sees the misuse of words not as a kind of 'irresponsibility' with regard to meaning, but as a responsibility to make fresh use of the language. Catachreses in Manson range from as simple a formulation as 'falling awake' (clear 'mis'-application of a term in a way which cannot properly be described as metaphorical) to a more fundamental reconfiguration of a text's grammar. This article aims first to identify and categorise catachresis in Manson's recent work along the boundary lines drawn by ancient and contemporary rhetoricians and theorists, and then to explain how that informs our reading of these poems. The reading takes as a starting point the productive wrongnesses that come out of the neo-Oulipian texts of Factitious Airs (2016), then moves to consider catachresis as one possible reference for the idea of 'frank rupture' (a deliberate breaking with the conventional meanings of words) in the longer texts of Poems of Frank Rupture (2014). Taking Gertrude Stein's poetics as a point of comparison, the article considers the notion of catachrestic grammar, and how this can develop over a longer text, as well as catachresis as traditionally considered at the level of the individual word. Ultimately it hopes to provide a new critical tool for thinking about those manoeuvres in Manson's work which cannot be described in the conventional vocabulary of poetic imagery.